The impact of immunosuppression on the duration and level of fecal shedding of E. Coli O157:H7 in calves - Sreerama, Sruti (Kansas State University, 2007)
Escherichia coli O157:H7 has emerged as a significant human food-borne pathogen over the past two decades. While cattle have been identified as the major reservoir of the pathogen, the dynamics of shedding are still largely unknown. The role immunosuppression may play on fecal shedding in cattle is explored. The first study determined whether immunosuppression induced by dexamethasone injections affects the level and duration of fecal shedding of E. coli O157. Six one week old Holstein bull calves were injected intramuscularly with dexamethasone and orally inoculated with 109 CFU of a mixture of three nalidixic-acid resistant strains of E. coli O157. Another five one week old Holstein bull calves, only inoculated with the E. coli O157, served as controls. All calves were necropsied and samples from the gastrointestinal tract were cultured. Dexamethasone treated calves shed at higher levels on days four and seven post-inoculation, but not thereafter. The data from this study suggest that there may be a time dependent correlation between dexamethasone immunosuppression and the concentration of E. coli O157 an animal will shed in the feces and that transient immunosuppression does not result in prolonged shedding of E. coli O157. The goal of the second study was to determine whether calves immunosuppressed by persistent infection with bovine viral diarrhea virus (BVDV) will shed E. coli O157 at a higher level and for a longer duration than a normal animal. Nine six to eight week old calves persistently infected with non-cytopathic BVDV and eight normal calves obtained from separate cow-calf operations were orally inoculated with 109 CFU of a mixture five nalidixic-acid resistant strains of E. coli O157. All calves were necropsied and samples from the gastrointestinal tract cultured. There was no statistical difference in the concentration of E. coli O157 shed or the duration of shedding between the persistently infected BVDV calves and the control calves throughout the length of the study. The data suggest that immunosuppression caused by persistent infection with non-cytopathic BVDV infection does not play a role in the level or duration of shedding of E. coli O157:H7 in calves.
Keywords: Escherichia coli O157; shedding; immunosuppression; Biology, Veterinary Science (0778)